Use of food labels by adolescents to make healthier choices on snacks: a cross-sectional study from Sri Lanka - Ishanka A. Talagala; Carukshi Arambepola (BMC, 2016)
Abstract Background Unhealthy snacking is commonly seen among adolescents. Therefore, use of food labels is promoted for making healthier choices on packaged snacks. This study was conducted to assess the use of food labels in making choices on packaged snack and its associated factors among adolescents. Methods A cross-sectional study was conducted in 2012 among 542 Grade 12 students in Sri Lanka. Eight classes were selected as 'clusters' for the study (two classes each from two schools that were selected randomly from each list of 'Girls only' and 'Boys only' schools in Colombo district). A self-administered questionnaire assessed their socio-demography, snacking behaviour, attitudes and nutrition knowledge related to food labels. Adolescents' use of labels was assessed by three practices (label reading frequency, attention paid to label contents and correct interpretation of six hypothetical labels of snacks). Based on total scores obtained for the three practices, 'satisfactory' (score ≥75th percentile mark) and 'unsatisfactory' (score <75th percentile mark) label users were identified. Using SPSS, associations were assessed at 0.05 significance level using Chi-square-test. Results Of the participants, 51 % were males; 61 % spent their pocket money at least once/week on packaged snacks; predominantly on biscuits (85 %) and cola-drinks (77 %) and 88 % selected snacks on their own. The majority (74.5 %) was frequent ('always' or 'most often') label readers with female predominance (p < 0.05). Over 74 % paid attention frequently to the brand name (75 %), price (85 %) and nutrition panel (81 %). Over 64 % were able to select the better food label when given a choice between two snacks, although some did it for reasons such as attractive label (63 %). The majority (84 %) had good knowledge (obtaining more than the 75th percentile mark) on interpreting labels. Although not statistically significant, 'unsatisfactory' label use was higher among males (73 %), purchasing power (70.4 %) and unhealthy snacking behaviour (73 %). In contrast, among the marketing strategies, identifying known brands (73.2 %) and imported products (75.8 %) as 'good' products were significantly associated with 'unsatisfactory' label use (p < 0.05). Conclusions Despite having good knowledge and positive attitudes, food label use is unsatisfactory among adolescents. Skills in reading labels should be addressed in the 'School canteen policy' in Sri Lanka.